A Simple Scheme for Realizing Six-Photon Entangled State Based on Cavity Quantum Electrodynamics (Journal of Atomic and Molecular Sciences, 2012)
A simple scheme is presented for generating six-photon entangled state with resonant interaction between a cascade type four-level atom and two three-mode cavities. In the proposed protocol, the quantum information is encoded on Fock states of the cavity fields. We solve Schrödinger equation and obtain quantum states of interaction system. The detection of the atom can collapse the cavity to the desired six-photon entangled state.